The vagina has reducing environment sufficient for activation of Trichomonas vaginalis cysteine proteinases. Issue 4 (August 1997) - Alderete, J F; Provenzano, D
Abstract : BACKGROUND: Trichomonas vaginalis, a worldwide distributed sexually transmitted protozoan, is remarkable for synthesis of numerous, distinct cysteine proteinases, the significance of which is evidenced by the presence in vivo of soluble proteinases in secretions and antiproteinase antibody in serum of patients with trichomonosis. These proteinases purportedly play a role in host parasitism and immune evasion. OBJECTIVE: It is known that for cysteine proteinases to be functional, they must be activated by disulphide reducing reagents. Whether or not the host vaginal environment has the reducing environment essential for activation of the trichomonad cysteine proteinases is unknown. Our goal, therefore, was to determine whether or not vaginal secretions had sufficient reducing power to activate the trichomonad proteinases. METHODS: 48 vaginal washes (VWs) from patients were assayed for reducing equivalents and a score in dithiothreitol (DTT) reducing equivalents was assigned to each VW. Activation of trichomonad cysteine proteinases was then tested under the range of reducing equivalents detected from VWs. The possible protective effect of hydrogen peroxide, an oxidising agent produced by some Lactobacillus species, on proteinase activity was also determined. RESULTS: Nine of 48 VWs (18.7%) possessed < or = 10 microM DTT reducing equivalents, four VWs (8.3%) had from 20 microM DTT to 40 microM DTT reducing equivalents, and most (50%) were between 10 microM to 15 microM. Overall, the range in VWs was from approximately 10 microM to 40 microM reducing equivalents. Importantly, data suggest differential proteinase activation over this in vivo range of reducing level. Only two T vaginalis cysteine proteinase activities were stimulated at 2.5 microM DTT in contrast with all proteinase activities present at 40 microM DTT, albeit quantitatively diminished compared with the activity at 1 mM DTT, the concentration routinely used in vitro. Finally, hydrogen peroxide reversibly neutralised all trichomonad proteinases. CONCLUSIONS: These results show that the vagina of women has a reducing environment adequate for activation of trichomonad proteinases. The data underscore that the host environment plays a role in the host-parasite interrelation. Finally, hypotheses can now be formulated to help explain resistance and susceptibility to infection commonly reported among women and between men and women with trichomonosis.